2011
DOI: 10.1111/j.1365-2753.2010.01613.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the degree of knowledge on oral cancer among general practitioners and dentists in Qazvin

Abstract: This study demonstrated an inadequate level of knowledge on oral cancers in both groups. Additional training in universities as well as continuing educational programmes on prevention and early detection of oral cancers is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…This delay in diagnosis is probably a result of a combination of late presentation by patients and missed diagnosis. Effective theoretical and practical education on oral cancer to general dentists and students should cover the areas of recognition of pre-cancerous and cancerous lesions, etiologic factors, and accurate clinical examination of all patients in particular those aged over forty (Borhan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This delay in diagnosis is probably a result of a combination of late presentation by patients and missed diagnosis. Effective theoretical and practical education on oral cancer to general dentists and students should cover the areas of recognition of pre-cancerous and cancerous lesions, etiologic factors, and accurate clinical examination of all patients in particular those aged over forty (Borhan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that five-year survival rate is 78% in cases of early diagnosis compared to advanced cases with only 19% survival rate (12). Although oral cavity is an accessible environment for dental examination, early detection rate of SCC has remained unchanged (2,13). It is mainly because SCC is usually painless in early stage (2).…”
Section: Contextmentioning
confidence: 99%
“…GMPs are unlikely to examine patient's oral mucosa routinely, unlikely to advise patients about risk factors for oral cancer, likely to identify few risk factors, technically poor at performing the nine steps of oral cancer screening examinations, and overall not confident in diagnosing OPMLs or oral cancers. [168][169][170][171][172][173] In addition, medical students entering the workforce have been trained with even less awareness, knowledge, confidence, and skills for performing opportunistic screening for oral cancer than their more experienced colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…[170][171][172][173] A recent study of 640 GDPs in Australia showed that over 90% regularly perform oral mucosal screening examinations for all patients. 31 Australian GDPs reported lack of training, confidence, time, and financial incentives as barriers to performing mucosal screening to at least some degree.…”
Section: General Medical and Dental Practitionersmentioning
confidence: 99%
See 1 more Smart Citation